An exploratory study of the relationship between epistemological beliefs and self-directed learning readiness - Boden, Carrie J. (Kansas State University, 2005)
The purpose of this study was to investigate the relationship between demographic and educational variables, epistemological beliefs as measured by Schommer’s Epistemological Questionnaire (SEQ), and learner perception of selfdirectedness as measured by Guglielmino’s Self-Directed Learning Readiness Scale (SDLRS). Participants in this study were undergraduate adult students at a private university in the Midwest region of the United States (N=394). The instruments were administered online during regularly scheduled courses. Data were analyzed at the p<.05 level of significance using Pearson product-moment correlations, factor analysis, stepwise multiple regression, and other statistical techniques. Results of this research included several significant correlations between demographic and educational variables, SEQ factors, and SDLRS total and factor scores. The educational variables of class standing, exposure to the humanities, and exposure to the social sciences significantly correlated with five SDLRS and SEQ total and factor scores. The greatest number of correlations occurred between SEQ factor 2, thinking for yourself is a waste of time, and the SDLRS factors of openness to learning opportunities, view of self as an effective and independent learner, independence and initiative in learning, responsibility for learning, and creativity. Other significant correlations with SEQ factors and SDLRS total and factor scores included age, gender, race, marital status, mother’s and father’s education level, credit earned through independent studies, cohort or non-cohort program type, grade point average, and exposure to learning contracts. Significant findings from the correlations of demographic and educational variables (p<.002) and SEQ factors (p<.05) with SDLRS total scores were entered into a stepwise multiple regression. One educational variable and three SEQ factors accounted for 25.7% of the variance in SDLRS total scores. Several suggestions for the development of expanded empirical and theoretical research initiatives and the improvement of practice were offered. This research provided a clear and compelling rationale for the establishment of adult degree programs which are grounded in the liberal arts, include both career and personal development activities, and allow for increased opportunities for learner self-direction to occur. These elements are necessary to build what Kegan (1994) called a developmental bridge for adult learners.
Keywords: Self-directed learning; Adult education; Epistemological beliefs; Guglielmino Self-Directed Learning Readiness Scale; Liberal arts; Schommer Epistemological Questionnaire; Education, Adult and Continuing (0516)Education, Curriculum and Instruction (0727)